2012
DOI: 10.5937/ekonhor1203151j
|View full text |Cite
|
Sign up to set email alerts
|

Risk management of portfolio securities

Abstract: Investment funds in diff erent types of fi nancial assets are motivated by investors' expectation to realize a profi t. Since the expected return is not always certain, the investor is faced with a risk of his investment not giving results in accordance with the expectations. Therefore, the consideration of risk by which the concrete placement is hampered should not be neglected or le$ to intuition. An incorrect risk assessment can result in a lack of the expected return or a loss of a capital investment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Diversification suits those investors on the financial market that cannot reliably estimate movements in the future, as well as those investors that have repugnance towards the risk (Rubinstein, 2002). The research papers have shown that weak correlation of securities reduces the risk without reducing the portfolio return (Jakšić, 2012). Markowitz's portfolio theory is the subject of research on different markets and in different periods of development, which shows that optimal portfolio forming is not the same in a different period (Agustini, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Diversification suits those investors on the financial market that cannot reliably estimate movements in the future, as well as those investors that have repugnance towards the risk (Rubinstein, 2002). The research papers have shown that weak correlation of securities reduces the risk without reducing the portfolio return (Jakšić, 2012). Markowitz's portfolio theory is the subject of research on different markets and in different periods of development, which shows that optimal portfolio forming is not the same in a different period (Agustini, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tržišni rizik predstavlja rizik od nepovoljnih kretanja cena finansijskih instrumenata. Međutim, dok je regulator primarno zainteresovan za aspekt rizika portfolija hartija od vrednosti (Jaksic, 2012), investitori su prevashodno zainteresovani za prinos, pa rizik posmatraju samo u kontekstu prinosa (realizovanih ili očekivanih). Po pravilu, portfolio menadžeri u izveštajima o performansama portfolija navode vrednost realizovanog prinosa po jedinici rizika za posmatrani period.…”
Section: Ekonomski Fakultet Univerziteta U Kragujevcuunclassified
“…Market risk ) is a risk resulting from adverse movements in the prices of liquid financial instruments. As long as regulators are concerned about the risk profiles of the portfolios under their consideration (Jaksic, 2012), investors seek return and only consider risk in relation to return (either realized or expected). As a rule, portfolio managers report on portfolio performance in terms of realized return per unit of risk taken in the observed period.…”
Section: Introductionmentioning
confidence: 99%